2021
DOI: 10.1038/s41586-021-03491-6
|View full text |Cite
|
Sign up to set email alerts
|

Drugs that inhibit TMEM16 proteins block SARS-CoV-2 spike-induced syncytia

Abstract: COVID-19 is a disease with unique characteristics that include lung thrombosis 1 , frequent diarrhoea 2 , abnormal activation of the inflammatory response 3 and rapid deterioration of lung function consistent with alveolar oedema 4 . The pathological substrate for these findings remains unknown. Here we show that the lungs of patients with COVID-19 contain infected pneumocytes with abnormal morphology and frequent multinucleation. The generation of these syncytia results from activation of the SARS-CoV-2 spike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
502
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 365 publications
(522 citation statements)
references
References 51 publications
19
502
0
1
Order By: Relevance
“…Furthermore, we also observed the loss of cilia in many of the syncytia, which could be responsible for a poor mucociliary clearance that impedes the evacuation of viral particles and pathogens. Taken together, our findings are in accordance with previous findings but highlight syncytium formation as an important mechanism to explain the spreading of SARS-CoV-2 and the physiopathology of bronchial epithelium infection (14, 43, 45, 46). Since the beginning of the COVID-19 pandemic, SARS-CoV-2 infection is more virulent in adults compared to children.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we also observed the loss of cilia in many of the syncytia, which could be responsible for a poor mucociliary clearance that impedes the evacuation of viral particles and pathogens. Taken together, our findings are in accordance with previous findings but highlight syncytium formation as an important mechanism to explain the spreading of SARS-CoV-2 and the physiopathology of bronchial epithelium infection (14, 43, 45, 46). Since the beginning of the COVID-19 pandemic, SARS-CoV-2 infection is more virulent in adults compared to children.…”
Section: Discussionsupporting
confidence: 93%
“…Virus infectivity and fusogenicity mediated by the PBCS is a key determinant of pathogenicity and transmissibility 22,28 and there are indications that giant cells/syncitia formation are associated with fatal disease 29 . We find that P681R is associated with enhanced capacity to induce cell-cell fusion and syncitia formation, and that P681R alone confers this ability on the B.1.617.1 spike with RBD mutations L452R and E484Q.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that syncytia formation by SARS-CoV-2 S can induce pyroptosis, and it has been proposed for other viral-mediated fusion events that cell death following syncytia formation can affect immune responses 60,61 . All this has led to an interest in the possibility that syncytia formation by SARS-CoV-2 is a potential target for therapeutic strategies 18,62 . Indeed, the process appears entirely dependent on the cell surface protease TMPRSS2 to make the activating S2' cleavage, whereas viral entry can be facilitated by either TMPRSS2 or lysosomal cathepsins 11,17 .…”
Section: Discussionmentioning
confidence: 99%